The Effectiveness of Online Learning at English Education Students - Rizkariani Sulaiman; Ery Ermianti (Didaktika: Jurnal Kependidikan, 2021)
Online learning is one of the alternative learning media specially made for lecturers and students of the Universitas Muslim Indonesia in carrying out the teaching and learning process during the COVID-19 pandemic, but its effectiveness is still questionable. This is what motivated the researcher to conduct research on the effectiveness of online learning. This study aims at determining the effectiveness, advantages, and disadvantages of online learning for English Education students Faculty of Letters Universitas Muslim Indonesia during the Covid 19 pandemic. The method used in this study was a mixed, quantitative, and qualitative method. The population in this study was students of the English Education Faculty of Letters Universitas Muslim Indonesia and the research sample was 41 students. To collect data, the researcher used a questionnaire in the form of a google form and used proportional stratified sampling in determining the research subject. The results of this research lead to evidence that online learning can help English Education students Faculty of Letters Universitas Muslim Indonesia attend lectures whenever and wherever they are.